KADAR DEBU SEMEN TERHIRUP MENGGUNAKAN PERSONAL DUST SAMPLER DAN GANGGUAN FAAL PARU PADA OPERATOR UNIT FINISH MILL - Glori Abdiningsih Rachmani (Universitas Airlangga, 2019)
Exposure to dust in the work environment is a potential factor that can cause impaired pulmonary function. Concentration of dust in the air is one factor that affects the severity caused. Higher exposure to dust in the air, increase the risk of impaired pulmonary function. The objective of the research was to analyze the exposure to respirable cement dust and pulmonary function impairment of Finish Mill operators in PT. Semen Indonesia, Tuban Regency. This study used a cross-sectional study design, with the number of sample using purposive sampling method as many as 10 people. The level of inhaled semen dust is measured using a Personal Dust Sampler (PDS). The characteristics of workers are also seen include age, length of employment, smoking habits, use of personal protective equipment and respiratory complaints felt. The results of this study were 90% of operators with respirable dust levels > 3 mg/m3. The highest respirable dust content was 26,7151 mg/m3. The lowest respirable dust content was 1.4665 mg/m3. In addition, 22.2% of operators who have inhaled dust levels > 3 mg/m3 have impaired pulmonary function. Conclusions can be drawn pulmonary function impairment more experienced by operators aged 36 - 45 years, with a working period of more than 15 years. Smoking habits and respiratory history may be seen from operator respiratory complaints.Keywords: finish mill operators, pulmonary function test, respirable cement dust.